FORMATION OF SUSTAINABLE COMMUNITY DEVELOPMENT MODELS CONSIDERING TOURIST LOGISTICS INFRASTRUCTURE - STEHNEI, Marianna; NOD, Orshoia; PETRICHKO, Maria; BERGHAUER, Sándor; OKSYMCHUK, Serhii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
This article explores tourism and logistics infrastructure's essence, components, and role in forming and implementing sustainable development models for territorial communities. The subject of the study is transport and logistics infrastructure and models of its organization in the context of ensuring the sustainable development of communities. The object of the study is the tourism and logistics infrastructure and territorial communities of the Zakarpattia region. The study examines the specifics of forming sustainable development models for territorial communities in the context of decentralization. Using the example of the Zakarpattia region, it has been determined that tourism is a crucial component of local communities' economic, social, and environmental development. The current state and challenges of tourism and logistics infrastructure in the Zakarpattia region have been analyzed. The essence, advantages, and challenges of forming tourism and logistics support models (innovative, integrated, polarized, decentralized) have been systematized in the context of their impact on the sustainable development of territories and communities. Considering the tourism potential and resources of the Zakarpattia region, an integrated model of tourism and logistics infrastructure with elements of innovation and diversification has been proposed. This model will contribute to the balanced development of the region, reduce the burden on popular destinations, expand access to remote and mountainous areas, and improve the quality of tourist services. It has been proven that a well-developed tourism and logistics infrastructure will foster sustainable community development through economic growth, social progress, and environmental security by attracting investments, creating jobs, and implementing green technologies.
Keywords: territorial communities; sustainable development model of territorial communities; tourism; tourism and logistics infrastructure; models of tourism and logistics organization